2018
DOI: 10.1159/000490249
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Folate Intake and Risk of Childhood Brain and Spinal Cord Tumors: A Systematic Review and Meta-Analysis

Abstract: Background: Many epidemiological studies have investigated the effect of maternal diet and prenatal multivitamin supplementation on pediatric cancer risk. Childhood brain and spinal cord tumors (CBSCT) have been attributed to different possible risk factors. Methods: We conducted a systematic review and meta-analysis on maternal folate intake before and during pregnancy and the risk of CBSCT. We systematically reviewed publications obtained by searching the Insitute for Scientific Information Web of Knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…In this study, there was no significant association between maternal folic acid supplementation and CBT (OR, 1.02; 95% CI, 0.88 to 1.19; p =0.78). This finding was different from the recently published meta-analysis by Chiavarini et al [48], who reported that maternal folic acid intake was inversely associated with the risk of childhood brain and spinal cord tumours (OR, 0.77; 95% CI, 0.67 to 0.88).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, there was no significant association between maternal folic acid supplementation and CBT (OR, 1.02; 95% CI, 0.88 to 1.19; p =0.78). This finding was different from the recently published meta-analysis by Chiavarini et al [48], who reported that maternal folic acid intake was inversely associated with the risk of childhood brain and spinal cord tumours (OR, 0.77; 95% CI, 0.67 to 0.88).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the results of subgroup analyses may not represent all the populations of the involved studies. (3) The number of studies regarding maternal alcohol and caffeinated beverages consumption, as well as the sample sizes in many subgroup analyses, is still insufficient. (4) Mothers exposed to maternal smoking and consumption of beverages during pregnancy are more likely to be exposed to these factors both before conception and after delivery.…”
Section: Bias Limitations and Strengthsmentioning
confidence: 99%
“…Evidence from animal studies has led to a hypothesis that the central nervous system is susceptible to carcinogenesis during the prenatal period [ 2 ]. Maternal exposures during pregnancy might play a crucial role in the risk of CBTs, as reported in two recent meta-analyses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of childhood CNS tumors is still poorly understood [2,3] and preventive measures to preclude the disease are lacking. A growing body of research has targeted parental lifestyle factors [4][5][6], occupational exposures [7,8], or environmental pollutants [9][10][11][12] as possible risk factors but has hitherto provided inconclusive evidence [2,3,13]. Certain genetic syndromes, exposure to high-dose ionizing radiation, and high or low birth weight [2,3,14,15] are the only wellestablished risk factors to date and those explain only a minor proportion (5-10%) of all cases [2,3].…”
Section: Introductionmentioning
confidence: 99%